Evaluation of the Comparative Genoprotective Effect of Daucus carota and Aloe vera - Yadav, Deepak; Prajapati, Manju (Journal of Neonatal Surgery, 2025)
Cancer is a deadly disease with a high incidence rate, with breast, ovarian, prostate, and lung cancer being the main types in women and men. In India, breast cancer cases are increasing among wealthy women. Chemotherapy remains the main treatment, but effective therapy depends on early diagnosis and progression stages. Plants have long been used as a source of medicines, with traditional medicine systems like Ayurveda, Unani, and Siddha using plant extracts for various cancer treatments. Natural products from medicinal plants have been discovered to be effective in cancer therapy, with 14 of the top 35 drugs in 2000 worldwide. Further studies could isolate bioactive compounds, reduce chemotherapy side effects, conduct clinical trials, pharmacokinetic studies, and conduct surveillance and post-marketing surveillance. Aloe barbadensis, a perennial, drought-resistant plant, is known as the healing plant due to its wound and burn healing properties. It has been used in health, beauty, medicine, and skin care for centuries. The pharmacologically active ingredients in aloe are concentrated in inner parenchymatous tissue called aloe gel and outer pericyclic tubules called aloe sap or aloe juice. These bioactive compounds are effective in treating various conditions, including burns, allergic reactions, rheumatoid arthritis, rheumatic fever, acid indigestion, ulcers, diabetes, skin diseases, dysentery, diarrhea, piles, and digestive system inflammatory conditions. Aloe vera is also used in cosmetic products to provide a healthy, supple skin look, reduce wrinkles, cure acne, rejuvenate, and give it a youthful glow. Dacus carota, also known as carrot, is a plant in the Apiaceae or Umbelliferae family, classified into twelve subspecies. The wild carrot was traditionally used for medicinal purposes by ancient Greeks and Romans, with its antioxidant, anticancer, anti-inflammatory, gastroprotective, hepatoprotective, antibacterial, and antifungal activities confirmed in-vitro and in-vivo over the past two decades. The study aims to assess the Genoprotective effect of Daucus carota and Aloe vera using Invitro and Invivo models for their toxicity analysis. The results suggest that the Genoprotective effect of the plan exctracts showed a concentration dependant potency and leads a way for a herbal approach for a successful Genoprotective agent.